2004
DOI: 10.1183/18106838.0102.130
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of wheezing and asthma presenting in early childhood

Abstract: Key pointsChildhood asthma and wheezing illness encompass a wide clinical spectrum.Most children with asthma first present before the age of 3 years.Coexistent atopy and initial disease severity carry a poor long-term prognosis.A switch from male to female predominance occurs at puberty.Good prognostic factors include presentation before 2 years of age and exclusively virally induced episodes.CME article: educational aimsTo identify the different types of wheezing illness in asthma that present in childhood.To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…Based on cohort studies, a breaking point at 2 years of age is considered appropriate, with the majority of those presenting symptoms before this age becoming asymptomatic by mid-childhood. 22 Consistent with another Dutch study in primary care, 20 we found that less than 40% of all children with a first prescription of asthma medication had a registered doctor diagnosis of asthma. The incremental change in the likelihood of having a doctor diagnosis of asthma with each repeated prescription of asthma medication found in our study ( Figure 2) is also in line with the findings of Zuidgeest et al However, both studies reveal that, even in children with prolonged use of asthma medication (and in children older than 6 years of age), a large proportion of children receive asthma medication without having a doctor diagnosis of asthma.…”
Section: Discussionsupporting
confidence: 78%
“…Based on cohort studies, a breaking point at 2 years of age is considered appropriate, with the majority of those presenting symptoms before this age becoming asymptomatic by mid-childhood. 22 Consistent with another Dutch study in primary care, 20 we found that less than 40% of all children with a first prescription of asthma medication had a registered doctor diagnosis of asthma. The incremental change in the likelihood of having a doctor diagnosis of asthma with each repeated prescription of asthma medication found in our study ( Figure 2) is also in line with the findings of Zuidgeest et al However, both studies reveal that, even in children with prolonged use of asthma medication (and in children older than 6 years of age), a large proportion of children receive asthma medication without having a doctor diagnosis of asthma.…”
Section: Discussionsupporting
confidence: 78%